Pengenalan Buku Kas Sebagai Upaya Pengaturan keuangan keluarga Kepada Para Ibu Rukun Tetangga 29 Kelurahan Sawah Lebar Kota Bengkulu - Susena, Karona Cahya; Nasution, Suswati; Hidayah, Nenden Restu; Yustanti, Nirta Vera; Ariantara, Yudi (Universitas Dehasen Bengkulu, 2022)
Management of family finances is very important, considering the many problems that occur due to the lack of skills in managing family finances. What often happens is an imbalance between income and expenditure, the term is